Distinct Serum and Fecal Metabolite Profiles Linking With Gut Microbiome in Older Adults With Frailty - Guo, Yan; Zhu, Guoqin; Wang, Fengliang; Zhang, Haoyu; Chen, Xin; Mao, Yan; Lv, Yifan; Xia, Fan; Jin, Yi; Ding, Guoxian; Yu, Jing (Frontiers in Medicine, 2022)
Frailty is a critical aging-related syndrome but the underlying metabolic mechanism remains poorly understood. The aim of this study is to identify novel biomarkers and reveal potential mechanisms of frailty based on integrated analysis of metabolome and gut microbiome. In this study, twenty subjects consisted of five middle-aged adults and fifteen older adults, of which fifteen older subjects were divided into three groups: non-frail, pre-frail and frail, with five subjects in each group. The presence of frailty, pre-frailty or non-frailty was established according to Physical Frailty Phenotype (PFP). We applied non-targeted metabolomics to serum and feces samples and used 16S rDNA gene sequencing to detect the fecal microbiome. The associations between metabolites and gut microbiota were analyzed by Spearman correlation analysis. Serum metabolic shifts in frailty mainly included Fatty acids and derivatives, Carbohydrates and Monosaccharides. Most of the metabolites belonging to these classes increased in the serum of frail older adults. Propylparaben was found to gradually decrease in non-frail, pre-frail and frail older adults. Distinct changes in fecal metabolite profiles and gut microbiota were also found among middle-aged adults, non-frail and frail older subjects. Relative abundance of Faecalibacteriu, Roseburia and Fusicatenibacter decreased while abundance of Parabacteroides and Bacteroides increased in frailty. The above altered microbes were associated with the changed serum metabolites in frailty, including Dodecanedioic acid, D-ribose, D-(-)-mannitol, Creatine and Indole, and their related fecal metabolites. The changed microbiome and related metabolites may be used as biomarkers of frailty and is worthy of further mechanistic studies.